Analisis Faktor-Faktor Yang Mendorong Keberhasilan Masyarakat Berwirausaha Pada UMKM Di Kabupaten Lombok Tengah NTB - Wiwik Julianti; I Made Suardana; Lalu Mimbar (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to analyze the factors that encourage the success of entrepreneurial communities in MSMEs in Central Lombok Regency, NTB. This type of research is associative and the sampling technique used is probability sampling technique. The sample used was 100 respondents to MSMEs in Central Lombok Regency. The results of the multiple linear regression analysis are Y = 0,445 + 0,562X1 + 0,341X2 + e Partially, internal factor variables with a significance of 0.000 <0.05, external factors with a significance of 0.001 <0.05 show a significant effect on the success of the community in entrepreneurship. Simultaneously the variables of internal factors and external factors with a significance of 0.000 <0.05 indicate a significant effect on the success of the community in entrepreneurship.